Online Learning Content Creation for Junior High School Teachers during the Covid-19 Pandemic - Pramudita, Brahmantya Aji; Aprillia, Bandiyah Sri; Pangaribuan, Porman; Ramdhani, Mohamad; Adam, Kharisma Bani (Universitas Muhammadiyah Surakarta, 2022)
The community service program from Telkom University aims to improve the ability and insight of learning technology using Camtasia Studio at SMPN 1 Baleendah. The method used in community service is a form of training or workshops where the participants, in this case are teachers, are given training for a maximum of 3 hours, instructors in this case are from Telkom University. The stages carried out in this training are broadly as follows: The stages of making or recording material content, the editing or editing stages of material content and the stages of uploading learning material content. Participation by partners is in the form of providing space, infrastructure such as laptops or computers (computer laboratory recommendations), internet networks, and teachers’ resources to be given Camtasia Studio training. Based on the results of the initial survey it was found that 15% had experience in making interactive videos by using programs other than Camtasia studio, and as many as 85% of the teachers are inexperienced in making interactive videos because they only use learning media based on whatsapps, zoom and google classroom. After the training, there was an increase in the skill level of making interactive videos for all participants. As many as 75% of the teachers strongly agree regarding the suitability of the programs held with the aim of carrying out activities. Lecturers and students are stated to be more friendly, faster and responsive in helping during the practical activities of creating interactive video content using Camtasia studio.